Determining the prognostic significance of PI3K/Akt/mTOR and JAK/STAT5 signaling pathways in pediatric acute lymphoblastic leukemia using single-cell analysis - Oliveira, Mariana Lobato de, 1991- (2016)
Tese de mestrado, Oncobiologia, Faculdade de Medicina, Universidade de Lisboa, 2015